Electrolyte, solid-state battery, preparation method of solid-state battery and power utilization device

The electrolyte composed of bromoacetonitrile and lithium difluorooxalatoborate addresses the low conductivity and impedance issues in solid-state batteries, enhancing lithium ion transmission and stability.

CN119208726APending Publication Date: 2024-12-27SHENZHEN POWER SUPPLY BUREAU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362686.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional solid-state batteries suffer from low ionic conductivity and high interface impedance between the solid electrolyte and the electrode, which hinders their performance and stability.

Method used

The use of an electrolyte comprising bromoacetonitrile and lithium difluorooxalatoborate, with a specific mass ratio, to enhance ionic conductivity and reduce interface impedance, is introduced.

Benefits of technology

The electrolyte improves lithium ion hopping frequency and electrode-solid electrolyte interface compatibility, leading to higher ionic conductivity and enhanced stability of the solid-state battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to an electrolyte, a solid-state battery, a preparation method of the solid-state battery and a power utilization device. The electrolyte comprises bromoacetonitrile and lithium difluoro (oxalato) borate. In the electrolyte, bromoacetonitrile has a relatively small dissolving sheath, has relatively good solubility on lithium difluoro (oxalato) borate, and can form a solvation sheath layer, so that the frequency hopping of lithium ions between adjacent conjugate sites in lithium difluoro (oxalato) borate is relatively high, and relatively high ionic conductivity is generated. When the electrolyte is used between a solid electrolyte and an electrode, the transmission of lithium ions at the interface of the solid electrolyte and the electrode can be promoted, the interface impedance between the solid electrolyte and the electrode is reduced, and the interface compatibility of the electrode and the solid electrolyte is improved, so that the stability of a solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a solid-state battery, a preparation method thereof, and an electrical device. Background Art

[0002] Solid-state batteries have attracted widespread attention due to their high safety, high energy density and long service life. However, the ionic conductivity of the solid electrolyte in traditional solid-state batteries is low, and the interface impedance between the solid electrolyte and the electrode is large.

[0003] Therefore, it is necessary to improve the traditional technology. Summary of the invention

[0004] Based on this, the present application provides an electrolyte, a solid-state battery and a preparation method thereof, and an electrical device with high ionic conductivity that can effectively reduce the interface impedance between the solid electrolyte and the electrode.

[0005] The technical solution of this application to solve the above technical problems is as follows.

[0006] In a first aspect of the present application, an electrolyte is provided, comprising bromoacetonitrile and lithium difluorooxalatoborate.

[0007] In some embodiments, in the electrolyte, the mass ratio of the lithium difluorooxalatoborate to the bromoacetonitrile is 1:3-15.

[0008] In some of the embodiments, in the electrolyte, the mass ratio of the lithium difluorooxalatoborate to the bromoacetonitrile is 1:5-10.

[0009] In a second aspect of the present application, a method for preparing an electrolyte is provided, comprising the following steps:

[0010] Bromoacetonitrile and lithium difluorooxalatoborate were mixed to prepare an electrolyte.

[0011] In a third aspect of the present application, there is provided the use of the above-mentioned electrolyte or the electrolyte prepared by the above-mentioned method for preparing the electrolyte in the preparation of a solid-state battery.

[0012] In a fourth aspect of the present application, a solid-state battery is provided, comprising a positive electrode, a solid electrolyte layer and a negative electrode, wherein the solid electrolyte layer is arranged between the positive electrode and the negative electrode, a first mutual contact layer is provided between the positive electrode and the solid electrolyte layer, a second mutual contact layer is provided between the solid electrolyte and the negative electrode, and at least one of the first mutual contact layer and the second mutual contact layer comprises the above-mentioned electrolyte or an electrolyte prepared by the above-mentioned electrolyte preparation method.

[0013] In some embodiments, in the solid-state battery, the ratio of the total mass of the electrolyte in the first mutual contact layer and the second mutual contact layer to the area of ​​the solid electrolyte is 0.05 mg / mm 2 ~0.8 mg / mm 2 .

[0014] In some of the embodiments, in the solid-state battery, the solid-state electrolyte includes at least one of LLTO, LATP, LAGP, LLZO, LLZTO and LLAZO; and / or

[0015] The positive electrode comprises at least one of LFP, NCM, NCA, LCO and LMO; and / or

[0016] The negative electrode includes at least one of metal lithium foil, graphite and lithium titanate.

[0017] In a fifth aspect of the present application, a method for preparing a solid-state battery is provided, comprising the following steps:

[0018] The positive electrode, the solid electrolyte layer and the negative electrode are assembled so that the solid electrolyte layer is arranged between the positive electrode and the negative electrode; a first mutual contact layer is arranged between the positive electrode and the solid electrolyte layer, and a second mutual contact layer is arranged between the solid electrolyte and the negative electrode; at least one of the first mutual contact layer and the second mutual contact layer includes the above-mentioned electrolyte or an electrolyte prepared by the above-mentioned electrolyte preparation method.

[0019] In a sixth aspect of the present application, there is provided an electrical device comprising the above-mentioned solid-state battery or a solid-state battery prepared by the above-mentioned method for preparing the solid-state battery.

[0020] Compared with the prior art, the electrolyte of the present application has the following beneficial effects:

[0021] The electrolyte of the present application includes bromoacetonitrile and lithium difluorooxalate borate. Bromoacetonitrile has a smaller dissolution sheath and better solubility in lithium difluorooxalate borate. It can form a solvation sheath, so that the lithium ion hopping frequency between adjacent conjugated sites in lithium difluorooxalate borate is higher, thereby having higher ionic conductivity.

[0022] Using the above-mentioned electrolyte between the solid electrolyte and the electrode can promote the transmission of lithium ions at the interface between the solid electrolyte and the electrode, reduce the interface impedance between the solid electrolyte and the electrode, and improve the electrode-solid electrolyte interface compatibility, thereby improving the stability of the solid-state battery. DETAILED DESCRIPTION

[0023] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0024] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0026] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0027] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0028] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0029] Solid-state batteries have many advantages over liquid batteries:

[0030] Higher safety: Liquid electrolytes are prone to leakage, posing the risk of combustion or even explosion; solid electrolytes are non-flammable and leak-proof, greatly reducing safety hazards. Even in extreme situations such as puncture, they can maintain good stability and will not spontaneously combust or explode.

[0031] Higher energy density: Solid-state batteries can store more electrical energy in the same volume or weight. The current energy density limit of liquid batteries is around 300 wh / kg, while solid-state batteries can reach more than 400 wh / kg, and the theoretical value can even reach 900wh / kg, which means that devices using solid-state batteries can have a longer range, such as electric vehicles.

[0032] Longer service life: Solid-state batteries can withstand more charge and discharge cycles, reducing the attenuation of battery performance. Compared with liquid batteries, solid-state batteries do not have problems such as corrosion and leakage caused by liquid electrolytes, nor do they produce problems such as lithium dendrites that are difficult to solve like liquid lithium batteries, so their overall service life is longer.

[0033] Wider operating temperature range: Solid-state batteries generally perform better than liquid batteries in high-temperature environments. Although their performance may not be as good as liquid batteries in low-temperature conditions, they have advantages in some application scenarios that require high-temperature stability.

[0034] The battery structure can be simplified: Since there is no liquid electrolyte, the material system of solid-state batteries can have more possibilities, and non-essential devices can be simplified at the pack level, thereby improving volume utilization.

[0035] Compared with polymer solid electrolytes, inorganic ceramic solid electrolytes have the following advantages:

[0036] High ion conductivity: Inorganic ceramic solid electrolytes generally have high lithium ion conductivity, which enables more efficient ion transport, helps reduce battery internal resistance, and improves battery charge and discharge performance and power output.

[0037] Good electrochemical stability: Inorganic ceramic solid electrolytes have a wider electrochemical stability window, can withstand higher voltages, and are not prone to decomposition or adverse reactions with electrode materials. This makes them suitable for high-voltage positive electrode materials, thereby increasing the energy density of the battery.

[0038] Good thermal stability: Inorganic ceramic materials generally have good thermal stability and are not prone to deformation, decomposition or combustion in high temperature environments. They can effectively improve battery safety and reduce the risk of thermal runaway.

[0039] High mechanical strength: Inorganic ceramic solid electrolytes have high mechanical strength and are not easily pierced by lithium dendrites, which helps to inhibit the growth of lithium dendrites, thereby extending the cycle life of the battery and improving the safety of the battery. However, polymer solid electrolytes are relatively soft and have low mechanical strength, and are less effective in inhibiting the growth of lithium dendrites.

[0040] Excellent chemical stability: Inorganic ceramic solid electrolytes are highly stable to environmental factors such as air and moisture, and are not prone to chemical reactions with the external environment, thus ensuring the performance stability of the electrolyte and the long-term reliability of the battery. However, polymer solid electrolytes may be affected by environmental factors to a certain extent.

[0041] An embodiment of the present application provides an electrolyte, including bromoacetonitrile (CBN) and lithium difluorooxalatoborate (LiODFB).

[0042] The electrolyte of the present application includes bromoacetonitrile and lithium difluorooxalate borate. Bromoacetonitrile has a smaller dissolving sheath and fast dissolving-dissolving ability, has good solubility in lithium difluorooxalate borate, can form a solvation sheath, and makes the lithium ion hopping frequency between adjacent conjugated sites in lithium difluorooxalate borate higher, thereby having higher ionic conductivity.

[0043] Using the above-mentioned electrolyte between the solid electrolyte and the electrode can promote the transmission of lithium ions at the interface between the solid electrolyte and the electrode, reduce the interface impedance between the solid electrolyte and the electrode, and improve the electrode-solid electrolyte interface compatibility, thereby improving the stability of the solid-state battery.

[0044] In some of the examples, the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile in the electrolyte is 1:3~15.

[0045] It can be understood that the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile includes but is not limited to 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, and in some examples, it can be within the range formed by any two of these point values ​​as end values, the same below.

[0046] In some of the examples, the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile in the electrolyte is 1:5~10.

[0047] In some of the examples, the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile in the electrolyte is 1:5~8.

[0048] In some of the examples, the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile in the electrolyte is 1:7~8.

[0049] Preferably, the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile is 1:8.

[0050] By controlling the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile, the ionic conductivity of the electrolyte can be effectively improved.

[0051] An embodiment of the present application provides a method for preparing an electrolyte, comprising the following steps:

[0052] Bromoacetonitrile and lithium difluorooxalatoborate were mixed to prepare an electrolyte.

[0053] At a specific temperature, lithium difluorooxalatoborate has good solubility in bromoacetonitrile.

[0054] It can be understood that the preparation method of the electrolyte provided in the present application can produce the above-mentioned electrolyte, and the characteristics of the above-mentioned electrolyte are suitable for the preparation method of the electrolyte.

[0055] In some of the examples, in the method for preparing the electrolyte, the mixing temperature is 50°C to 90°C.

[0056] It will be appreciated that the mixing temperature includes, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, and 90°C.

[0057] In some of the examples, in the method for preparing the electrolyte, the mixing temperature is 70°C to 80°C.

[0058] The electrolyte prepared by the preparation method of the electrolyte provided in the present application has a high ionic conductivity and is used between a solid electrolyte and an electrode to reduce the interface impedance between the solid electrolyte and the electrode and improve the stability of the solid-state battery.

[0059] One embodiment of the present application provides the use of the above-mentioned electrolyte or the electrolyte prepared by the above-mentioned method for preparing the electrolyte in the preparation of a solid-state battery.

[0060] Another embodiment of the present application provides a solid-state battery, including a positive electrode, a solid electrolyte layer and a negative electrode, the solid electrolyte layer is arranged between the positive electrode and the negative electrode, there is a first mutual contact layer between the positive electrode and the solid electrolyte layer, there is a second mutual contact layer between the solid electrolyte and the negative electrode, at least one of the first mutual contact layer and the second mutual contact layer includes the above-mentioned electrolyte or an electrolyte prepared by the above-mentioned electrolyte preparation method.

[0061] The solid-state battery provided in the present application, including the above-mentioned electrolyte or the electrolyte prepared by the above-mentioned electrolyte preparation method, can give the solid-state battery a higher ionic conductivity, and the interface impedance between the solid electrolyte and the electrode in the solid-state battery is low, and the solid-state battery has better cycle performance.

[0062] It can be understood that the first mutual contact layer includes a first surface layer of the positive electrode facing the solid electrolyte layer and a second surface layer of the electrolyte layer facing the positive electrode, and the first surface layer and the second surface layer are in contact with each other. Further, the electrolyte can be located in the first surface layer or in the second surface layer, or there are electrolytes in both the first surface layer and the second surface layer. Further, the positive electrode includes a current collector and a positive electrode active layer on the surface of the current collector, and the thickness of the first surface layer can be the thickness of part or all of the positive electrode active layer.

[0063] Similarly, the second mutual contact layer includes a third surface layer of the negative electrode facing the solid electrolyte layer and a fourth surface layer of the electrolyte layer facing the negative electrode, and the third surface layer and the fourth surface layer are in contact with each other. Further, the electrolyte may be located in the third surface layer or in the fourth surface layer, or there may be electrolyte in both the third surface layer and the fourth surface layer. Further, the negative electrode includes a current collector and a negative electrode active layer on the surface of the current collector, and the thickness of the third surface layer may be the thickness of part or all of the negative electrode active layer.

[0064] Only one of the first mutual contact layer and the second mutual contact layer may include the above electrolyte or the electrolyte prepared by the above electrolyte preparation method, or both may include the above electrolyte or the electrolyte prepared by the above electrolyte preparation method.

[0065] In some examples, in the solid-state battery, the ratio of the total mass of the electrolyte in the first mutual contact layer and the second mutual contact layer to the area of ​​the solid electrolyte is 0.05 mg / mm 2 ~0.8 mg / mm 2 .

[0066] It is understood that the total mass ratio of the electrolyte in the first mutual contact layer and the second mutual contact layer to the area ratio of the solid electrolyte includes but is not limited to 0.05 mg / mm 2, 0.1 mg / mm 2 , 0.15 mg / mm 2 , 0.2 mg / mm 2 , 0.25mg / mm 2 , 0.3 mg / mm 2 , 0.35 mg / mm 2 , 0.4 mg / mm 2 , 0.45 mg / mm 2 , 0.5 mg / mm 2 , 0.55 mg / mm 2 , 0.6mg / mm 2 , 0.65 mg / mm 2 , 0.7 mg / mm 2 , 0.75 mg / mm 2 , 0.8 mg / mm 2 .

[0067] In some examples, in the solid-state battery, the ratio of the total mass of the electrolyte in the first mutual contact layer and the second mutual contact layer to the area of ​​the solid electrolyte is 0.05 mg / mm 2 ~0.5 mg / mm 2 .

[0068] In some examples, in the solid-state battery, the ratio of the total mass of the electrolyte in the first mutual contact layer and the second mutual contact layer to the area of ​​the solid electrolyte is 0.2 mg / mm 2 ~0.4 mg / mm 2 .

[0069] Preferably, the total mass ratio of the electrolyte in the first mutual contact layer and the second mutual contact layer to the area ratio of the solid electrolyte is 0.25 mg / mm 2 ~0.3 mg / mm 2 .

[0070] In some of these examples, the solid-state battery includes a solid-state lithium battery.

[0071] In some of the examples, in the solid-state battery, the solid electrolyte includes an inorganic ceramic solid electrolyte. In some of the examples, in the solid-state battery, the solid electrolyte includes at least one of LLTO (lithium lanthanum titanate), LATP (lithium aluminum titanium phosphate), LAGP (lithium aluminum germanium phosphate), LLZO (lithium lanthanum zirconate), LLZTO (lithium lanthanum zirconium titanium oxide), and LLAZO (lithium lanthanum aluminum zirconium oxide).

[0072] Preferably, the solid-state electrolyte comprises LLTO.

[0073] In some of these examples, in the solid-state battery, the positive electrode includes at least one of LFP (lithium iron phosphate), NCM (lithium nickel cobalt manganese oxide), NCA (lithium nickel cobalt aluminum oxide), LCO (lithium cobalt oxide) and LMO (lithium manganese oxide).

[0074] Preferably, the positive electrode comprises LFP.

[0075] In some of these examples, in the solid-state battery, the negative electrode includes at least one of metallic lithium foil, graphite, and lithium titanate.

[0076] An embodiment of the present application provides a method for preparing a solid-state battery, comprising the following steps:

[0077] The positive electrode, the solid electrolyte layer and the negative electrode are assembled so that the solid electrolyte layer is arranged between the positive electrode and the negative electrode; a first mutual contact layer is arranged between the positive electrode and the solid electrolyte layer, and a second mutual contact layer is arranged between the solid electrolyte and the negative electrode; at least one of the first mutual contact layer and the second mutual contact layer includes the above-mentioned electrolyte or an electrolyte prepared by the above-mentioned electrolyte preparation method.

[0078] In some of the examples, in the method for preparing a solid-state battery, the above-mentioned electrolyte or the electrolyte prepared by the above-mentioned method for preparing the electrolyte is placed between the positive electrode and the solid electrolyte and / or between the solid electrolyte and the negative electrode by a wetting manner.

[0079] In some of the examples, in the method for preparing a solid-state battery, the wetting step includes: dropping the above electrolyte or the electrolyte prepared by the above electrolyte preparation method onto the surface of at least one of the positive electrode, the solid electrolyte and the negative electrode. It is understood that after wetting, the positive electrode, the solid electrolyte layer and the negative electrode are assembled.

[0080] In some of the examples, in the method for preparing a solid-state battery, the positive electrode and the solid electrolyte are wetted with the above-mentioned electrolyte or an electrolyte prepared by the above-mentioned method for preparing the electrolyte, and then assembled with the negative electrode.

[0081] One embodiment of the present application provides an electrical device, comprising the above-mentioned solid-state battery or a solid-state battery prepared by the above-mentioned method for preparing the solid-state battery.

[0082] It is understood that electrical devices include but are not limited to at least one of power tools, electronic devices, electric vehicles or large energy storage devices. Among them, power tools use solid-state batteries as driving power to move parts, including but not limited to electric drills, etc.; electronic devices use solid-state batteries as operating power to perform various functions, including but not limited to mobile phones, laptops, desktop computers or electronic watches, etc.; electric vehicles rely on solid-state batteries as driving power to operate, including but not limited to electric vehicles, etc.; large energy storage devices use solid-state batteries as energy storage units, including but not limited to substations or wind turbines, etc.

[0083] The electrical device provided in the present application includes the above-mentioned solid-state battery and can obtain the same effect as the above-mentioned solid-state battery.

[0084] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0085] Example 1

[0086] Lithium difluorooxalatoborate and bromoacetonitrile in a mass ratio of 1:10 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0087] Example 2

[0088] Lithium difluorooxalatoborate and bromoacetonitrile in a mass ratio of 1:8 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0089] Example 3

[0090] Lithium difluorooxalatoborate and bromoacetonitrile in a mass ratio of 1:6 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0091] Example 4

[0092] Lithium difluorooxalatoborate and bromoacetonitrile in a mass ratio of 1:5 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0093] Comparative Example 1

[0094] Dissolve bromoacetonitrile at 80°C to obtain bromoacetonitrile solution.

[0095] Comparative Example 2

[0096] The method is substantially the same as Example 4, except that bromoacetonitrile is replaced with an equal mass of ethylene carbonate, as follows:

[0097] Lithium difluorooxalatoborate and ethylene carbonate in a mass ratio of 1:5 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0098] Comparative Example 3

[0099] The method is substantially the same as Example 4, except that bromoacetonitrile is replaced with an equal mass of difluoroacetonitrile, as follows:

[0100] Lithium difluorooxalatoborate and difluoroacetonitrile in a mass ratio of 1:5 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0101] Comparative Example 4

[0102] The method is basically the same as Example 4, except that lithium difluorooxalatoborate is replaced with lithium hexafluorophosphate of equal mass, as follows:

[0103] Lithium hexafluorophosphate and bromoacetonitrile in a mass ratio of 1:5 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0104] Comparative Example 5

[0105] The method is basically the same as Example 4, except that lithium difluorooxalatoborate is replaced with lithium bisoxalatoborate of equal mass, as follows:

[0106] Lithium bis(oxalatoborate) and bromoacetonitrile in a mass ratio of 1:5 were dissolved and mixed at 80° C. to prepare an electrolyte.

[0107] The ionic conductivity of the electrolytes prepared in the embodiments and comparative examples at 25° C. is tested, and the results are shown in Table 1.

[0108] Table 1

[0109]

[0110] Lithium difluorooxalate borate / bromoacetonitrile has a small dissolving sheath and fast dissolution-dissolution ability. Lithium difluorooxalate borate is easily dissolved by bromoacetonitrile, and the short residence time will lead to Li + The hopping frequency is high, thus producing a higher conductivity. The ion conductivity of the electrolyte prepared in Example 2 is as high as 32 mS / cm at 25°C. Bromoacetonitrile and lithium difluorooxalatoborate are compounded to obtain an electrolyte material that can be used independently, achieving good ion conduction.

[0111] The LLTO solid electrolyte was pressed into a sheet with a pressure of 10 MPa, a thickness of 200 microns and a diameter of 19 mm; the electrolyte prepared in Example 2 (the mass ratio of lithium difluorooxalatoborate to bromoacetonitrile was 1:8) was used to wet the lithium iron phosphate LFP positive electrode and the LLTO solid electrolyte sheet, and the solid-state lithium metal battery was assembled with the negative electrode (lithium foil).

[0112] Although the liquid electrolyte wetting interface is introduced, due to its small content (the mass ratio of the electrolyte to the area of ​​the solid electrolyte is 0.05 mg / mm 2 ~0.8 mg / mm 2), the overall performance of solid-state batteries, especially safety, including diaphragm puncture, leakage, flammability, etc., will not be affected by the trace addition of liquid electrolyte.

[0113] The total usage of the electrolyte prepared in Example 2 is 0 mg, 20 mg, 40 mg, 60 mg, 80 mg, 100 mg, 120 mg, and 140 mg, respectively, which are marked as solid-state lithium metal batteries 1 to 8, respectively; the usage of the electrolyte prepared in Comparative Examples 1 to Comparative Examples 4 is 20 mg, respectively marked as solid-state lithium metal batteries 9 to 12.

[0114] The solid-state lithium metal batteries 1 to 8 were subjected to electrochemical impedance spectroscopy tests and cycle tests (after 200 cycles), respectively. The cycle current was 1 C, and the capacity retention rate after 200 cycles was recorded. The test results are shown in Table 2.

[0115] Table 2

[0116]

[0117] As can be seen from Tables 1 and 2, the combination of bromoacetonitrile and lithium difluorooxalate borate has a higher lithium ion conductivity, and can also infiltrate the ceramic LLTO electrolyte and electrode interface, promote the transmission of lithium ions at the interface, improve the electrode-solid electrolyte interface compatibility of the solid-state battery, and improve the stability of the battery. Increasing the amount of electrolyte added within a certain range, the synergistic effect of reducing the interface impedance is enhanced; after reaching a certain amount, the effect of reducing the interface impedance reaches saturation; continuing to increase the amount of electrolyte added does not further promote the circulation of the solid-state lithium metal battery, but instead increases the impedance.

[0118] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0119] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. An electrolyte, characterized in that: These include bromoacetonitrile and lithium difluorooxalate borate.

2. The electrolyte according to claim 1, characterized in that The mass ratio of the lithium difluorooxalatoborate to the bromoacetonitrile is 1:3-15.

3. The electrolyte according to claim 2, characterized in that The mass ratio of the lithium difluorooxalatoborate to the bromoacetonitrile is 1:5-10.

4. A method for preparing an electrolyte, characterized in that: The following steps are involved: Bromoacetonitrile and lithium difluorooxalatoborate were mixed to prepare an electrolyte.

5. Use of the electrolyte according to any one of claims 1 to 3 or the electrolyte prepared by the method for preparing the electrolyte according to claim 4 in preparing a solid-state battery.

6. A solid-state battery, characterized in that: The invention comprises a positive electrode, a solid electrolyte layer and a negative electrode, wherein the solid electrolyte layer is arranged between the positive electrode and the negative electrode, a first mutual contact layer is provided between the positive electrode and the solid electrolyte layer, a second mutual contact layer is provided between the solid electrolyte and the negative electrode, and at least one of the first mutual contact layer and the second mutual contact layer comprises the electrolyte according to any one of claims 1 to 3 or the electrolyte prepared by the method for preparing the electrolyte according to claim 4.

7. The solid-state battery according to claim 6, characterized in that The ratio of the total mass of the electrolyte in the first mutual contact layer and the second mutual contact layer to the area of ​​the solid electrolyte is 0.05 mg / mm 2 ~0.8 mg / mm 2 .

8. The solid-state battery according to any one of claims 6 to 7, characterized in that: The solid electrolyte comprises at least one of LLTO, LATP, LAGP, LLZO, LLZTO and LLAZO; and / or The positive electrode comprises at least one of LFP, NCM, NCA, LCO and LMO; and / or The negative electrode includes at least one of metal lithium foil, graphite and lithium titanate.

9. A method for preparing a solid-state battery, characterized in that: The following steps are involved: The positive electrode, the solid electrolyte layer and the negative electrode are assembled so that the solid electrolyte layer is arranged between the positive electrode and the negative electrode; and a first mutual contact layer is arranged between the positive electrode and the solid electrolyte layer, and a second mutual contact layer is arranged between the solid electrolyte and the negative electrode; at least one of the first mutual contact layer and the second mutual contact layer comprises the electrolyte as described in any one of claims 1 to 3 or the electrolyte prepared by the method for preparing the electrolyte as described in claim 4.

10. An electrical device, characterized in that: A solid-state battery comprising the solid-state battery as described in any one of claims 6 to 8 or a solid-state battery prepared by the method for preparing the solid-state battery as described in claim 9.